2007
DOI: 10.1055/s-2006-955874
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Fibrous Histiocytoma of the Lung

Abstract: Although surgical resection of MFH is the treatment of choice in MFH, the results are unsatisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…We must take into consideration the fact that primary MFH of the lung is extremely rare (0,2% of the pulmonary neoplasms) with only about 50 cases been reported in the literature [4]. There must be no evidence of another primary site as determined by physical and radiologic exam before a MFH can be considered a lung primary tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We must take into consideration the fact that primary MFH of the lung is extremely rare (0,2% of the pulmonary neoplasms) with only about 50 cases been reported in the literature [4]. There must be no evidence of another primary site as determined by physical and radiologic exam before a MFH can be considered a lung primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, survival after complete surgical resection in cases of primary lung MFH has been reported to be better than for other pulmonary sarcomas [4]. Many clinicopathologic factors are significally related to disease free specific survival (DSS) and metastasis free survival (MFS), including age, tumor size-depth, classification stage, histologic type and grade.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Although a study reported that 33% of patients who received combination chemotherapy showed partial response, MFH is usually resistant to chemotherapy or radiotherapy. 3,5 A previous study revealed a 5-year survival rate of 58% and a 10-year survival rate of 38%. 6 Surgical resection is the best treatment option when the disease is limited.…”
Section: Discussionmentioning
confidence: 97%
“…6 Surgical resection is the best treatment option when the disease is limited. 5,7 A few cases of MFH arising from the pleura and diaphragm have shown aggressive clinical features. 8,9 However, the bronchus and trachea are extremely rare sites for MFH, and to our knowledge, there are only 10 cases reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…MFH is a soft tissue sarcoma mainly occuring in the soft tissues, especially in the extremities and trunk. MFH is an aggressive malignancy with high potential of local recurrence and distant metastasis3-5. Surgery is treatment of choice even with recurrence and metastasis6.…”
Section: Introductionmentioning
confidence: 99%